Most significant reduction of cardiovascular events in patients undergoing lipoproteinapheresis due to raised Lp(a) levels – A multicenter observational study. (November 2017) - Schatz, U.; Tselmin, S.; Müller, G.; Julius, U.; Hohenstein, B.; Fischer, S.; Bornstein, S.R.
Abstract: Objectives: Lipoprotein(a) (Lp(a)) is an independent cardiovascular (CV) risk factor, predisposing to premature and progressive CV events. Lipoproteinapheresis (LA) is the only efficacious therapy for reducing Lp(a). Data comparing the clinical efficacy of LA with respect to reduction of CV events in subjects with elevated Lp(a) versus LDL-C versus both disorders is scarce. We aimed to perform this comparison in a multicenter observational study. Methods: 113 LA patients from 8 apheresis centers were included (mean age 56.3 years). They were divided into 3 groups: Group I: Lp(a) < 600 mg/l, LDL-C > 2.6 mmol/l, Group II: Lp(a) > 600 mg/l, LDL-C < 2.6 mmol/l, and Group III: Lp(a) > 600 mg/l, LDL-C > 2.6 mmol/l. CV events were documented 2 years before versus 2 years after LA start. Results: Before start of LA Group II showed the highest CV event rate (p 0.001). Group III had a higher CV event rate than Group I (p 0.03). During LA there was a significant reduction of CV events/patient in all vessel beds (1.22 ± 1.16 versus 0.33 ± 0.75, p < 0.001). The highest CV event rate during LA was seen in coronaries followed by peripheral arteries, cerebrovascular events were least common. Greater CV event reduction rates were achieved in patients with isolated Lp(a) elevation (−77%, p < 0.001) and in patients with Lp(a) and LDL-C elevation (−74%, p < 0.001) than in subjects with isolated hypercholesterolemia (−53%, p 0.06). Conclusion: This study demonstrates that patients with Lp(a) elevation benefit most from LA treatment. Prospective trials to confirm these data are warranted.